Murine Sarcoma and Leukemia Viruses: Assay Using Clonal Lines of Contact-Inhibited Mouse Cells - Jainchill, John L. (1969)
A continuous cell line of highly contact-inhibited cells (NIH/3T3) has been developed from NIH Swiss mouse embryo cultures. Its growth properties are similar to those of 3T3 and BALB/3T3. Although 3T3 is relatively insensitive to focus formation by murine sarcoma viruses, cloned lines of both NIH/3T3 and BALB/3T3 have been isolated that are highly sensitive to sarcoma virus focus formation and leukemia virus growth. The sensitivity and specificity are comparable to those found with primary embryo cells. MSV-transformed lines of NIH/3T3 have been obtained.